Ti-Mo cast alloys for biomedical applications. Anodic behavior and passive film properties - Oliveira, N. T.C. [UNESP] (2010)
Casting of Ti-Mo alloys having different Mo content (4 to 20 wt%) was performed by arcmelting of pure metals. These alloys present interesting features for potential biomedical applications, e.g., in artificial proteases, owing the favorable characteristics of Ti alloys: apart from mechanical properties and good osseointegration, the strong corrosion resistance in biological environment and the low toxicity of their corrosion products The corrosion and anodic behavior of the different alloys was investigated in different electrolytes, including neutral, acidic and chloride-containing solutions. A strong tendency to passivation was observed, caused by the oxygen affinity of the metallic material. However, partial Mo dissolution is likely to occur at very low pH Composition and solid-state properties of the passive films were studied by ex-situ XPS, in-situ photoelectrochemical and impedance experiments. Films were found to consist of a mixed oxide phase, mainly containing TiO2 and bearing small concentrations of MoO3. The latter depends on starting alloy composition and film thickness As a result, also the behavior of the passive films depends on these two factors. In fact thin films or films grown on alloys bearing a small Mo content display n-type semiconducting behavior, analogous to what reported for pure TiO2. On the contrary, films grown on alloys with higher Mo content are more resistive and change their behavior from semiconducting to insulating with increasing thickness. © 2010 Nova Science Publishers, Inc. All rights reserved.